1999
DOI: 10.2514/2.2543
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Fatigue Behavior of Bonded Composite Repairs

Abstract: Composite patches are bonded to a cracked metallic surface either symmetrically (double sided) or unsymmetrically (single sided) to extend service life. The stresses in the metallic panel are greatly affected by the repair symmetry. Unsymmetric repairs present the greatest challenge because of the presence of out-of-plane bending. Thermal residual stresses are present because of the thermal coef cient mismatch of the patch and the aluminum plate. Debonding along an adhesive-adherend interface can reduce the pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
17
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(21 citation statements)
references
References 7 publications
4
17
0
Order By: Relevance
“…It is firstly noted that the asymptotic behaviour is visible for the two cases and there is a reduction of the asymptotic value about 10% by the use of double symmetric patch, it means that the fatigue life of the structure can be improved considerably. This tendency is in agreement with the analysis of Klug et al [14] whom showed that the use of a double patch increase twice as much the fatigue life of the structure compared with the single patch. It can also be see in Fig.…”
Section: Resultssupporting
confidence: 89%
“…It is firstly noted that the asymptotic behaviour is visible for the two cases and there is a reduction of the asymptotic value about 10% by the use of double symmetric patch, it means that the fatigue life of the structure can be improved considerably. This tendency is in agreement with the analysis of Klug et al [14] whom showed that the use of a double patch increase twice as much the fatigue life of the structure compared with the single patch. It can also be see in Fig.…”
Section: Resultssupporting
confidence: 89%
“…As a result, the crack growth rate does not depend on of crack length according to the Paris law. Klug (Klug et al, 1999) investigated the fatigue behaviour of pre-cracked 2024-T3 aluminum plates repaired with a bonded carbon/epoxy patch. Single sided repairs were found to provide about a 4-5 times improvement in the fatigue life.…”
Section: Introductionmentioning
confidence: 99%
“…They indicated that the bonded repair patches are effective for repairing the fatigue and/or corrosion cracks in an airframe. Residual strength and stress concentration in the repaired part were discussed by many researchers because they depended on various details such as surface treatment, geometry of patch, material properties and adhesive thickness [3][4][5][6][7][8][9][10][11][12]. They reported that the composite patch is debonded under cyclic loading condition and additionally the debonding cause the strength deterioration of the substrates.…”
Section: Introductionmentioning
confidence: 97%